Characterization of bioactive compounds in commercial olive leaf extracts, and olive leaves and their infusions. Issue 8 (15th July 2019) - Medina, Eduardo; Romero, Concepción; García, Pedro; Brenes, Manuel
Abstract : A large spectrum of beneficial health properties has been attributed to olive leaves. Abstract : A large spectrum of beneficial health properties has been attributed to olive leaves. This study was undertaken to characterize the bioactive compounds of commercial olive leaf extracts and olive leaves and their infusions. High variability of bioactive compounds was found among commercial samples. Polyphenol was detected in a range of 44–108 g kg −1 and 7.5–250 g kg −1 for olive leaves and olive leaf extracts, respectively. The main phenol was oleuropein, representing 74–94% of total phenols. However, only 17–26% of polyphenols were diffused to the aqueous phases when olive leaf infusions were prepared. Triterpenic acids were found in a range of 26–37 g kg −1 in olive leaves, but not detected in the infusions. Hence, the absence of the latter substances and the low oleuropein diffusion in olive leaf infusions make new studies necessary to maximize the presence of these bioactive compounds in the final product.